The Place of Gymnastics in A Person's Life and the Terms Used in Training (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Anatatsiya: this article is of great importance in the formation of children and teenagers with physical gymnastics. Diverse means of gymnastics, and the term of the  methods using the primary functions of physical education, success, the strength of resolveto a wider understanding about the terms are given which will help you out. Gymnastics very large hygiene-healthy‘lomlashtirish the importance of also there are.